2019
DOI: 10.1002/jclp.22908
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of and attitudes toward CBT, DBT, and ACT in an acute psychiatric sample

Abstract: Objective Treatment utilization for psychiatric illness is low, perhaps influenced by limited consumer knowledge of evidence‐based psychological treatments (EBPTs). To inform consumer‐directed dissemination efforts, we characterized preferences, beliefs, and knowledge about specific EBPTs (cognitive behavioral therapy [CBT], dialectical behavior therapy [DBT], and acceptance and commitment therapy [ACT]); and examined potential sociodemographic and treatment history correlates. Method Before receiving treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 76 publications
1
8
1
Order By: Relevance
“…Although research support for clinical and tertiary treatments exists, these treatments are often intended for those who have already made suicide attempts or have been hospitalized for suicide-related reasons and they likely only have a minimal effect on suicide rates of the overall population [4,5]. This may be because of limited availability and postvention focus.…”
Section: Introductionmentioning
confidence: 99%
“…Although research support for clinical and tertiary treatments exists, these treatments are often intended for those who have already made suicide attempts or have been hospitalized for suicide-related reasons and they likely only have a minimal effect on suicide rates of the overall population [4,5]. This may be because of limited availability and postvention focus.…”
Section: Introductionmentioning
confidence: 99%
“…Literature on DBT-informed PH programs is also scarce, with some studies examining combined CBT and DBT (Beard et al, 2017) and another examining client attitudes towards DBT, CBT, and Acceptance and Commitment Therapy (ACT; Kuckertz et al, 2020). In terms of DBT specific PH programs, there is some preliminary evidence that DBT can be an effective treatment when utilized in this setting, specifically for individuals with BPD (Lenz & Del Conte, 2018) and eating disorders (Brown et al, 2020).…”
mentioning
confidence: 99%
“…Since there is no validated Arabic scale to help answer our research questions, the survey contents were first identified from four different scales in English (Pierce and Pearce, 2003 ; Donovan et al, 2015 ; Berg et al, 2019 ; Kuckertz et al, 2020 ). Questions were reorganized by the research team, underwent one-way translation into Arabic, and were then reviewed by a panel consisting of a child psychiatrist, child psychologist, and adult psychiatrist.…”
Section: Methodsmentioning
confidence: 99%
“…5. Attitude toward CBT (questions 32–37): We used the Psychological Treatment Consumer Questionnaire (PTCQ) (Kuckertz et al, 2020 ). We have modified the Familiarity section with specific evidence-based psychological treatments to be suitable for CBT typically offered to children.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation